Individuals at risk of seropositive rheumatoid arthritis: the evolving story. (21st October 2019) - Rantapää Dahlqvist, S.; Andrade, F.
Abstract: The aetiology of the autoimmune disease rheumatoid arthritis (RA) involves a complex interplay between genetic and environmental factors that initiate many years before the onset of clinical symptoms. These interactions likely include both protective and susceptibility factors which together determine the risk of developing RA. More than 100 susceptibility loci have been linked to RA. The strongest association is with HLA‐DRB1 alleles encoding antigen presenting molecules containing a unique sequence in the peptide‐binding grove called the 'shared epitope'. Female sex, infections during childhood, lifestyle habits (e.g. smoking and diet) and distinct microbial agents, amongst many others, are interacting risk factors thought to contribute to RA pathogenesis by dysregulating the immune system in individuals with genetic susceptibility. Interestingly, patients with RA develop autoantibodies many years before the clinical onset of disease, providing strong evidence that the lack of tolerance to arthritogenic antigens is amongst the earliest events in the initiation of seropositive RA. Here, we will discuss the clinical and mechanistic evidence surrounding the role of different environmental and genetic factors in the phases leading to the production of autoantibodies and the initiation of symptomatic RA. Understanding this complexity is critical in order to develop tools to identify drivers of disease initiation and propagation and to develop preventive therapeutics. Abstract :